2022
DOI: 10.1111/nph.18442
|View full text |Cite
|
Sign up to set email alerts
|

A competition‐attenuation mechanism modulates thermoresponsive growth at warm temperatures in plants

Abstract: Global warming has profound impact on growth and development, and plants constantly adjust their internal circadian clock to cope with external environment. However, how clockassociated genes fine-tune thermoresponsive growth in plants is little understood.We found that loss-of-function mutation of REVEILLE5 (RVE5) reduces the expression of circadian gene EARLY FLOWERING 4 (ELF4) in Arabidopsis, and confers accelerated hypocotyl growth under warm-temperature conditions.Both RVE5 and CIRCADIAN CLOCK ASSOCIATED … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…The growth and development of plants have high requirements on environmental temperature. As sessile organisms, plants have evolved various mechanisms to sense environmental temperature and adapt to natural 29,30 . Histone methylation also plays an important role in this [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…The growth and development of plants have high requirements on environmental temperature. As sessile organisms, plants have evolved various mechanisms to sense environmental temperature and adapt to natural 29,30 . Histone methylation also plays an important role in this [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…The growth and development of plants have high requirements on environmental temperature. As sessile organisms, plants have evolved various mechanisms to sense environmental temperature and adapt to natural 28,29 . Histone methylation also plays an important role in this [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…In response to both red light and elevated ambient temperature, CCA1 interacts with SHB1 and then promotes PIF4 expression through targeting the PIF4 promoter, therefore desensitizing the light responses for optimal photomorphogenesis and enhancing plant thermomorphogenesis for better survival under elevated ambient temperatures [140]. Recent research has also found another clock-associated gene-mediated balancing thermoresponsive growth system in plants by modulating the level of ELF4 by CCA1 and REVEILLE5 (RVE5) at warm temperatures [141]. In Arabidopsis, both RVE5 and CCA1 are transcriptional repressors and accumulate at warm temperatures, which can reduce the expression of ELF4 to promote hypocotyl growth.…”
Section: Light Signal and Temperature Signal Integration Through Pif4mentioning
confidence: 99%